REGISTRATION AND MANAGEMENT INFORMATION SYSTEM DESIGN OF POST PARTNERS - Muhamad Irfan Anshory; KamiliaAfnan Husna; FakhriDzulfiqar Zain; FajarAolia Nugraha; Parlindungan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Along with the development of information technology and increasing company activity, the need for information and data processing is needed in various fields and impactful for all services and especially for information providers for companies/agencies who need a management system quickly, precisely, and accurately. One is the process of registering a Post partner at the Post office of Cianjur Regency, especially in the current marketing section of the post partner registration level which is quite high. Post Partner Registration is still done manually and still uses the registration form in registering so those prospective partners who want to register are required to come to the Office for registration. The absence of the system for the registration of the postal Partner enrollment report is automatically used for auditing purposes containing the postal partner registrant report. The Waterfall method is used as the research method in this research. The initial stage begins with the analysis of using BPMN as a description of the ongoing process that is the business process procedure of Post Partner registration and the recapitulation of the Post partner registration report at the Post Office Cianjur Regency. For implementation modeling, this system using UML modeling consists of the modeling process, data, activity, and management.